Animated Video Based on a Contextual Approach to Improve Pronunciation and Contextual Understanding in the Material "I Want an Ice Cream Cone" for Fifth Grade Students - Ketut Arini; I Wayan Widiana; Gede Wira Bayu (Jurnal Edutech Undiksha, 2025)
Learning media plays an important role in enhancing students’ motivation and interest in learning, which can directly impact their understanding. However, many teachers still neglect the use of learning media in English subjects. This often leads to difficulties in English pronunciation and comprehension among students. This study aims to analyze the effectiveness of animation video-based learning media using a specific approach. The development research employed the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. The research subjects were 26 fifth-grade students. Data collection methods and instruments used questionnaires. The results of the study showed that the developed product had high validity, with an average score of 0.86 for the media aspect and 0.9 for the material aspect, indicating that the product is highly feasible for use. The practicality of the media, based on students’ responses, obtained an average score of 90.8%, which falls into the very good category. The results of the correlated t-test showed a significance value (2-tailed) of 0.001 or p < 0.05, thus it can be concluded that the animation video media is effective in improving pronunciation and comprehension of fifth-grade elementary school students. The implication of this research is that it can serve as a reference and reading material for teachers or readers in implementing enjoyable learning through the use of animation video media.